UNUSUAL OBRUCHEVELLA REPRESENTATIVES FROM THE WENDIAN DEPOSITS OF THE SIBERIAN CRATON - Golovenok V.K.; Belova M.Yu.; Avdeyeva V.I. (My University, 1990)
Researchers have found the microfossils of the genus Obruchevella Reitlinger, 1948 to be an extremely interesting group of very old microorganisms. Because of their characteristic helical structure, they are easy to identify both in thin sections and in synthetic preparates obtained by macerating the rock. Their extensive geographic distribution, considerable taxonomic variety and changes in size with time impart a high biostratigraphic potential to the Obruchevella representatives. With their use it is now possible to determine the relative age of the deposits containing them very reliably and to correlate sections quite distant from each other.